REALISASI PERENCANAAN DAN PELAKSANAAN TATA KELOLA KEUANGAN PEMERINTAH DESA - Warka Syachbrani; Muhammad Yahya (BJRM (Bongaya Journal of Research in Management), 2018)
This research is aimed to find out Village Financial Management in Indonesia. Descriptive qualitative research applied to analyzed primary and secondary data. The data were collected through interview and documentation technique. The data were analyzed by collecting, reducing, presenting data, concluding and verifying so the researcher can draw the final conclusion. The data validity checked by triangulation techniques and member checks. The results indicate that the management of village finances as a whole was not in accordance with the regulations. In the implementation stage, the village government has lower creativity in managing village finances.